New weak interaction signal in the SU(2)_1⊗SU(2)_2⊗U(1)_Y model - Vo , Quoc Phong; Nguyen , Thi Trang (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
According to the framework of Model (2-2-1 model), (be like in the standard model), and decays will be discussed. The decay width is equal to 2.1 GeV, consistently to SM and experimental data. The decay width is very large, in which the main contribution to this decay is the channel containing exotic quarks. Furthermore, it is found that the lepton rate decay of accounts for the bulk.